2009
DOI: 10.1002/jsfa.3800
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fermented soy product on the fecal microbiota of rats fed on a beef‐based animal diet

Abstract: The results indicate that the ingestion of this fermented soy product did not lead to significant changes in the fecal microbiota of the rats fed on a beef-based diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 32 publications
2
37
1
Order By: Relevance
“…43 Moreover, in vivo studies with probiotic soy products have been also performed and differences on fecal microbiota have been reported. Bedani et al, 44 analyzed bacterial genus composition in rats faeces that were administered the Enterococcus faecium CRL 183 probiotic microorganism with a soy product, either as a pure cell suspension or as a fermented product. Data were compared to microbial changes observed in rats treated with the unfermented soy product.…”
Section: Soy Productsmentioning
confidence: 99%
“…43 Moreover, in vivo studies with probiotic soy products have been also performed and differences on fecal microbiota have been reported. Bedani et al, 44 analyzed bacterial genus composition in rats faeces that were administered the Enterococcus faecium CRL 183 probiotic microorganism with a soy product, either as a pure cell suspension or as a fermented product. Data were compared to microbial changes observed in rats treated with the unfermented soy product.…”
Section: Soy Productsmentioning
confidence: 99%
“…In vitro and in vivo studies showed that Enterococcus faecium CRL 183 is able to adhere to the intestinal cells, resists the gastrointestinal environment and colonizes the large intestine of rats, thus satisfying the requirement for a probiotic microorganism [122,123]. Furthermore, this strain has no antibiotic resistance and no virulence factors, ensuring its safe use as a starter culture [121].…”
Section: Effects Of Enterococcus Faecium Crl 183 On Intestinal Microbmentioning
confidence: 99%
“…Enterococcus faecium CRL 183 has been investigated by our research group for about 20 years, with the objective of defining its functional properties in the free form or associated with food products [122,123,124,125,126,127,128,129,130].…”
Section: Effects Of Enterococcus Faecium Crl 183 On Intestinal Microbmentioning
confidence: 99%
See 2 more Smart Citations